2021
DOI: 10.1088/1755-1315/666/6/062140
|View full text |Cite
|
Sign up to set email alerts
|

Taxation Instruments for the Support of Research and Advanced Development Expenses in the Manufacturing Sector of the Economy

Abstract: The goal of this research is studying the results achieved by using the existing taxation instruments regulating the creation of R&D expenses during the profits tax calculation and payment in the manufacturing sector of the economy of the Russian Federation. The main methods of this research are the analysis and the generalization of regulatory documents, as well as the mathematical representation based on the extrapolation of empiric data on the structure of R&D expenses incurred within 2012-2018 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Concentrated in key areas and critical links of the industrial chain [2], these clusters have demonstrated remarkable resilience, exceptional innovation capabilities and unmistakable leadership, thereby becoming a vital force in achieving sustained industrial growth, bolstering the core incentives of the manufacturing sector and safeguarding the stability of industrial supply chains [3]. Therefore, it is imperative to examine the impact of local fiscal and tax incentives on industrial clusters [4] and to further refine the support system for cluster policies, particularly in the realms of finance and taxation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrated in key areas and critical links of the industrial chain [2], these clusters have demonstrated remarkable resilience, exceptional innovation capabilities and unmistakable leadership, thereby becoming a vital force in achieving sustained industrial growth, bolstering the core incentives of the manufacturing sector and safeguarding the stability of industrial supply chains [3]. Therefore, it is imperative to examine the impact of local fiscal and tax incentives on industrial clusters [4] and to further refine the support system for cluster policies, particularly in the realms of finance and taxation [5,6].…”
Section: Introductionmentioning
confidence: 99%